Destabilization of fine solids suspended in oil media through wettability modification and water-assisted agglomeration. (15th October 2019) - Liu, Jing; Cui, Xin; Santander, Camila; Tan, Xiaoli; Liu, Qi; Zeng, Hongbo
Graphical abstract: Highlights: A two-step method was developed for destabilizing fine solids in cyclohexane. PEG-PPG-PEG modified solids wettability and water triggered agglomeration of solids. The two-step method showed high settling rate and low residual solid content. Nanoscale interaction forces among solids, PEG-PPG-PEG and water were studied. Abstract: Removing fine solids suspended in aqueous or oil media is crucial in many chemical, petroleum and environmental engineering processes with ever-increasing demands on improving product quality and meeting waste management standard. In oil industry, the removal of fine mineral solids is required to achieve high-quality oil products but remains a great challenge. This difficulty is due to hydrophobic and oleophilic nature of the mineral matters and small dimension of fine particulates. Here we introduce a two-step agglomeration method to destabilize bitumen-coated silica particles in cyclohexane by simply modifying their surface wettability using the amphiphilic polymer poly(ethylene glycol)-block-poly(propylene glycol)-block-poly(ethylene glycol) (PEG-PPG-PEG), and then adding a small amount of water to trigger the formation of large particle aggregates. By sedimentation tests, we demonstrate that the two-step method can significantly enhance settling rate of the particles and reduce content of residual solids in the supernatant simultaneously. The underlying physical interaction mechanisms have been investigated using atomic force microscope (AFM) and quartz crystal microbalance with dissipation monitoring (QCM-D). The results suggest that PEG-PPG-PEG can readily adsorb to the bitumen-coated silica surface, thereby altering the surface from hydrophobic to hydrophilic and tuning its interaction with added water drops from repulsion to attraction in cyclohexane. This work provides useful insights into the development of effective strategies of removing suspended fine solids from oil media in petroleum production processes.